CYBERSECURITY COSTS IN AN ENTERPRISE UNIT - Antczak, Joanna (Edukacja Ekonomistów i Menedżerów, 2020)
Operation in the cyberspace of every business unit is unavoidable. Most commercial transactions, marketing activities, e-mail contact with employees or contractors are carried out using virtual space. The purpose of the article is to identify and analyze selected costs for cybersecurity of an enterprise. Costs related to cybersecurity constitute a new category in the management of an enterprise. Considering the costs at the enterprise level, two areas should be discussed: on the one hand, those incurred to prevent cyber threats and on the other one, the costs of offsetting the negative effects of cyber-attacks. For the sake of stable operation and at the same time development in the future, the management should strengthen activities in the field of information security, which is related to costs that will minimize the risk of cyber-attacks.